As canções de Camargo Guarnieri e Suzanna de Campos: um estudo para a interpretação - Pimenta, Josani Keunecke [UNESP] (2015)
The partnership between the poet Suzanna de Campos and the composer Camargo Guarnieri resulted in 18 art songs for voice and piano. In the current work, we present the main poetical and musical characteristics of each of the songs by those artists, offering, thus, a host of information and data that aim at serving as inspiration for the interpreter. When studying the poem, we presented the original text, its form, rhythm, meter and sonority. When studying the music, we pro vided information about the melody, the rhythm, the dynamics, the accompaniment and the form of the song. The musical aspects were highlighted using the text as lens, being as it was the first inspiration to the composer and it is through it that interpret ers can uncover the secrets of the song, so that the listener receives the plenitude of its poetical and musical meaning. Through the study of the art songs, we could evidence an intimate relationship between Guarnieri's vocal lines and the free prolation of the Brazilian Portuguese. The methodology proposed and used for studying the songs is the result of the compilation of ideas and suggestions from various musicologists and the author herself and, beyond contributing to the interpretative riches of the 18 songs studied, may serve as a model for the study of other songs. A survey of the main compositional stylistic characteristics of the songs was undertaken, with the objective of getting the reader acquainted with Guarnieri's writing traits. All of the 18 art songs were edited using the composer's manuscripts and this editoration includes phonetic transcriptions and translations into English.